Hubungan Pemakaian KB Suntik 3 Bulan Dengan Kejadian Spotting Pada Akseptor KB Di Puskesmas Manunggal Jaya Kabupaten Nabire - Nur Khasanah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Contraception is preventing the fertilization of an egg by a sperm cell (conception) or preventing the fertilized egg from attaching to the uterine wall. There are various methods of using contraception, one of which is using hormonal contraceptive methods, namely injection/injection contraception. Injection contraception is an injectable contraceptive. which is injected into the body over a certain period of time, then enters the blood vessels, and is absorbed little by little by the body to prevent pregnancy. The injectable contraceptives used are norethisterone enanthate, depo medroxy progesterone acetate (DMPA), and cyclofem. One of the modern contraceptives used DMPA is often used containing depo medroxy progesterone acetate as much as 150 mg with an efficacy of up to 3 months. This drug was tried in 1958 to treat habitual abortion and endometriosis, and it turns out that in the treatment of habitual abortion, infertility often occurs after the pregnancy ends. Depo-Provera as a contraceptive drug turns out to be quite effective and safe in family planning services. The assumption that Depo-Provera can cause cancer of the cervix or breasts in women who use it has not been clearly proven. Planned contraception is an attempt to space or plan the number and distance pregnancy by using contraception (BKKBN.2012).